The deposition of atmospheric microplastics in Jakarta-Indonesia: The coastal urban area. (January 2022) - Purwiyanto, Anna Ida Sunaryo; Prartono, Tri; Riani, Etty; Naulita, Yuli; Cordova, Muhammad Reza; Koropitan, Alan Frendy
Abstract: The air pollution in Jakarta has been recorded regularly; meanwhile, the information of atmospheric microplastics is still unknown. This study examines the characteristics (shape, size, and polymer) and deposition rate of atmospheric microplastics in Jakarta. The sample was obtained by putting a rain gauge for 12 months. All microplastic samples were analyzed for polymer using FT-IR. The lowest to the highest percentage of atmospheric microplastic based on shape were foam<fragment<fiber, meanwhile based on size were of 500–1000 μm < 300–500 μm. The detected polymers included polyester, polystyrene, polybutadiene, and polyethylene. The microplastics deposition rate ranged from 3 to 40 particles m −2 d −1, with an average of 15 particles m −2 d −1 . The rainy season's deposition rate (23.422 particles m −2 d −1 ) was higher than the dry season (5.745 particles m −2 d −1 ). Our study proves that the atmospheric microplastic exists in Jakarta's air and needs to be considered to monitor by the government regularly. Highlights: The deposition rate of atmospheric microplastic in the rainy season 4 times fold than the dry season. The meteorological factors (rainfall and wind speed) significantly influenced the deposition rate. The atmospheric microplastic size significantly affected the deposition. The atmospheric microplastics in Jakarta are derived from local activity emissions.